Perlindungan Data Pribadi Penerima Pinjaman Dalam Transaksi Pinjam Meminjam Uang Berbasis Teknologi Informasi (Peer To Peer Lending) - Agusta, Hendrawan (Jurnal Hukum & Pembangunan, 2020)
The development of information technology is very rapid, the collaboration between information technology and various fields of life bring in to various kinds of innovations that make peoples lives easier. Innovations in information technology bring in to new business models which in turn can produce efficiency for the community. The information technology revolution continues to grow and now entering the financial sector which is highly regulated. Collaboration between information technology and finance bring in to Financial Technology (Fintech), which is information technology-based money-lending (Peer to Peer Lending/P2P Lending). It is easier for people to access their financial needs through P2P Lending. On the other hand, challenges arise in P2P Lending regarding data protection (personal data, transaction data and financial data). In this research, only the personal data of the Borrower will be discussed, where the personal data needs to be protected so there is no misuse that causes legal problems.